A polymer superplasticizer with star-shaped topological structure and its preparation process and application
By blending polymer superplasticizer with star topology in all-solid-state lithium batteries with star topology and lithium-conducting polymers to construct a composite topology, the problems of lithium-ion transmission restricted under room temperature and poor stability under high pressure are solved, and the synchronous improvement of lithium-conducting performance and high-pressure stability are achieved.
Patent Information
- Application Number
- CN202211211836.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The polymer electrolytes of existing all-solid lithium batteries are limited in lithium ion transmission under room temperature conditions and have poor stability at high pressure, making it difficult to match high-voltage positive electrode materials.
A polymer superplasticizer with a star topology is used to blend the branched polymer arm with lithium conduction polymer to construct a composite topology, improve the solubility of lithium salt and lithium conduction properties, while maintaining the self-supporting properties of the film.
Without reducing the mechanical strength of the membrane, the room temperature lithium conduction performance and high-voltage stability are significantly improved, achieving the improvement of lithium ion conductivity and optimization of charge and discharge performance.
Smart Images

Figure CN115636917B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy storage functional polymer synthesis and application, and specifically is a polymer superplasticizer with a star topological structure and a preparation process and application thereof. Background Art
[0002] Lithium batteries are typical representatives of high-energy-density electrochemical energy storage devices. Influenced by the increasing demand for energy density and battery safety, all-solid-state lithium batteries have become an important research direction, and all-solid-state polymer electrolytes, which are the core components with high flexibility, excellent processing performance and high stability, have attracted great attention.
[0003] At present, the production process of lithium-conducting polymers represented by polyethylene oxide (PEO) and related all-solid-state polymer electrolyte lithium batteries has become mature. However, the intrinsic high crystallinity of polymers at room temperature seriously inhibits the transmission of lithium ions between lithium-conducting segments and brings about a large electrolyte-electrode interface resistance. To solve this problem, researchers often use methods such as polymer blending, grafting or plasticization modification to improve the flexibility of traditional polymer molecules, destroy the crystal region and inhibit crystallization. However, while these methods promote the improvement of the room temperature ion conductivity of the electrolyte, they also significantly reduce the stability of the polymer phase, interface compatibility and mechanical properties of the membrane. Therefore, how to achieve the simultaneous improvement of the ionic conductivity and charge and discharge stability of the polymer electrolyte while taking into account the self-supporting performance of the membrane is gradually becoming a key research direction in the field of solid-state battery research. In addition, with the increasing demand for high-energy-density power batteries, polymer electrolytes that can match high-voltage cathode materials have also become a major research hotspot. The abundant terminal hydroxyl groups of PEO molecules are more susceptible to oxidation at higher voltages, which in turn produces an uneven oxide layer between the positive electrode and the electrolyte interface, affecting the stable lithium conduction and causing overcharging due to the continuous decomposition of the electrolyte in the high-voltage range. Therefore, the highest voltage that the traditional PEO-based electrolyte can match is only 3.8 V, which is difficult to adapt to the high-voltage positive electrode. Superplasticizer is a polymer plasticizer with a composite topological structure and rich terminal functional groups. Compared with traditional plasticizers, superplasticizers have better compatibility with polymer matrices, no phase separation during use, and special topological structures and terminal functional groups make them have better plasticizing properties in polymer chemistry and physics. While interacting with the main polymer molecular segments, they can construct new interchain entanglements, thereby completing plasticization while maintaining the self-supporting properties of the polymer film. In addition, the rich terminal modifiable groups of superplasticizers can be grafted with groups that promote film stability to achieve a significant improvement in high-voltage stability. Inspired by this, superplasticizers that combine the three properties of "plasticization, blending, and molecular topological modification" are bound to effectively promote the improvement of the room temperature ion conductivity of polymer electrolytes. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a polymer superplasticizer with a star topological structure and its preparation process and application. The superplasticizer provided by the present invention has the advantages of simple synthesis, high plasticization efficiency, good compatibility with lithium-conducting polymers, good high-voltage stability, good lithium salt solubility, etc. It can form a superplasticizing blending system with lithium-conducting polymers represented by PEO, and achieve simultaneous improvement of ionic conductivity and high-voltage stability without sacrificing the mechanical strength of the membrane.
[0005] The technical solution adopted by the present invention is as follows: a polymer superplasticizer with a star-shaped topological structure, the superplasticizer comprising a first core layer (Core 1, C1), a second core layer (Core 2, C2), and a polymer arm (Arm, A);
[0006] The polymer superplasticizer with star-shaped topological structure is referred to as H x P y mxD z , where H, P, and mP are the abbreviations of C1, C2, and A (branched polyamine, branched polyether, and capped polyethylene glycol monomethyl ether), respectively, and x, y, and z are the codes for different component components.
[0007] The first core layer (C1) is one of branched polyethyleneimine, branched polyamide-amine, and branched polyethylene glycol amine;
[0008] The second core layer (C2) is one or more of branched polyglycidol, branched polypropylene oxide, branched polybutylene oxide, and branched poly 3-methyl-3-oxetane methanol;
[0009] The polymer arm (A) is a difunctional isocyanate-terminated polyethylene glycol monomethyl ether, and is bonded to the second core layer via a urea bond or a urethane bond.
[0010] The preparation process of the polymer superplasticizer with a star-shaped topological structure can be divided into five steps: preparation of a macromolecular initiator, initiation of polymerization, termination of polymerization, end group modification and product purification.
[0011] In particular, the above-mentioned macromolecular initiator preparation process can be divided into two steps: C1 macromolecular hydroxylation and hydroxylated macromolecular deprotonation:
[0012] (1) Hydroxylation of C1 macromolecules: Under argon protection, a certain mass of branched C1 macromolecules is fully dissolved in a specific solvent and heated to a specific temperature. A certain amount of glycidol monomer is added to the above solution at a certain dropwise rate. After the dropwise addition is completed, the reaction is allowed to proceed overnight. The system is then cooled to room temperature, acetone is precipitated, and the product is dried in vacuo.
[0013] Preferably, the molecular weight of the branched C1 macromolecule is between 1800 and 200000;
[0014] Preferably, the specific solvent can be one or more of anhydrous methanol, anhydrous ethanol, and anhydrous tetrahydrofuran, and the concentration of the polymer solution is 0.025 g / mL to 0.5 g / mL;
[0015] Preferably, the polymer solution is heated at a temperature between 40 and 65 o Between C;
[0016] Preferably, the amount of glycidol monomer added is the amount of all active hydrogen and other substances of the C1 macromolecule, and the dropwise addition speed is between 0.15 mL / min and 0.6 mL / min.
[0017] (2) Deprotonation of hydroxylated macromolecules: The hydroxylated C1 macromolecules are fully dissolved in a specific solvent, and a certain amount of Lewis base solution is injected under argon protection. The deprotonation is carried out at 40 degrees for 2 hours. After that, the viscous liquid with most of the solvent is depressurized and continued to be deprotonated for 2 hours. Finally, the solvent is drained at 60 degrees to obtain a foamy deprotonated macromolecular initiator.
[0018] Preferably, the specific solvent may be one or more of anhydrous methanol, anhydrous ethanol, and anhydrous tetrahydrofuran. The solvent used for the Lewis base solution is consistent with the hydroxylated macromolecular solvent, and the concentration of the Lewis base solution is between 3 and 5 mol / L.
[0019] Preferably, the deprotonating agent may be one or more of potassium methoxide, sodium methoxide, sodium hydride, and cesium hydroxide, and the added amount is 0.05-1 of the molar equivalent of the hydroxyl group of the polymer.
[0020] In particular, the above-mentioned initiation polymerization process can be divided into two steps: secondary dissolution of the macromolecular initiator and addition of the glycidol monomer. Specifically, the obtained foamy macromolecular initiator is fully dissolved by adding a specific high-boiling point polar aprotic solvent at a certain temperature, then the temperature is raised to the polymerization temperature, and the C2 monomer is slowly added dropwise into the system at a constant speed under high-speed stirring. After the addition is completed, the polymerization reaction is carried out for more than 6 hours.
[0021] Preferably, the secondary dissolution temperature of the initiator is 40 to 60 o C, select one or more of the high boiling point polar aprotic solvents selected from anhydrous dioxane, anhydrous N,N-dimethylformamide, N-methylpyrrolidone, and diethylene glycol dimethyl ether, and prepare a polymer solution with a concentration of 0.05 g / mL to 0.5 g / mL.
[0022] Preferably, the polymerization temperature is 95 to 120 o C.
[0023] Preferably, the monomer dropwise addition speed is 0.1-0.5 mL / min, and the dropwise addition amount is 10%-100% of the mass of the deprotonated polymer added.
[0024] In particular, the above-mentioned termination polymerization process can be divided into two steps: active initiation end group quenching and proton exchange. Specifically, after the reaction is completed, a certain volume of anhydrous methanol is added to the reaction system to quench the reaction, and the product solution flows through a pre-activated strong acid cation exchange resin at a certain flow rate to remove the terminal metal ions, and then the solvent is spin-dried, and the product is vacuum dried to obtain a polyamine-ether core-shell structure hyperbranched polymer.
[0025] Preferably, the amount of methanol added is 1-10 mL.
[0026] Preferably, the ion exchange resin treatment flow rate is 0.1-2 mL / min.
[0027] In particular, the above end group modification process can be divided into three steps: polyethylene glycol monomethyl ether end group activation, polyurethane reaction and product purification:
[0028] (1) Activation of polyethylene glycol monomethyl ether end groups: Polyethylene glycol monomethyl ether with different molecular weights is dissolved in a certain volume of a specific polar aprotic solvent. A certain amount of difunctional isocyanate is slowly dripped into the solution under the condition of anhydrous and oxygen-free and heating at 40 degrees, and the temperature is maintained for 2 hours.
[0029] Preferably, the molecular weight of the polyethylene glycol monomethyl ether is 500-5000.
[0030] Preferably, the polar aprotic solvent is one or more of anhydrous N,N-dimethylformamide, anhydrous N,N-dimethylacetamide, and anhydrous N-methylpyrrolidone, and the concentration of the polymer solution is 0.3-1 g / mL.
[0031] Preferably, the above-mentioned bifunctional isocyanate is one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, isophorone diisocyanate, and m-xylylene diisocyanate, and its isocyanate molar equivalent is twice the hydroxyl equivalent of the above-mentioned polyethylene glycol monomethyl ether.
[0032] (2) Polyurethane reaction: a certain amount of polyamine-ether is dissolved in a certain volume of a specific polar aprotic solvent. Under the protection of argon, a syringe is injected into the above-mentioned terminal activated monohydroxyl linear polymer solution to cause a polyurethane reaction between hydroxyl and isocyanate. The system temperature is raised to 60 degrees and the reaction is carried out for 2 hours.
[0033] Preferably, the molar amount of the polyamine-ether hydroxyl group is equal to that of the terminal activated monohydroxy linear polymer, and the polar aprotic solvent and solution concentration are selected to be consistent with the conditions of the monohydroxy linear polymer activation process.
[0034] In particular, the purification process of the above product is as follows: after the reaction is stopped and the system is cooled to room temperature, the above reaction product solution is treated by dialysis to remove a small amount of unreacted monomers. The reaction product solution is placed in a pre-activated specific molecular weight cut-off dialysis bag, dialyzed for 2 days under stirring conditions (new dialysis solvent is replaced every 8 hours), and then most of the solvent is removed by rotary evaporation. The solid obtained by rotary evaporation is then vacuum dried at a certain temperature to obtain the final product.
[0035] Preferably, the molecular weight cut-off of the dialysis bag is 1000-14000, and the molecular weight cut-off is determined according to the molecular weight of the selected C1 macromolecule and polyethylene glycol monomethyl ether, and the dialysis solvent is water or anhydrous ethanol.
[0036] Preferably, the vacuum drying temperature is 60 to 100 o C.
[0037] In the process of constructing an all-solid-state polymer electrolyte, the first core layer of the superplasticizer has typical amorphous characteristics. It provides abundant grafting sites on the basis of significantly inhibiting the crystallization of PEO, making it possible to construct a composite topological structure. In addition, its abundant amino groups can effectively promote the dissociation of lithium salts and improve the lithium conductivity of the system. The second core layer of the superplasticizer further expands its branching degree, and its branched lithium-philic units with a similar composition to PEO can participate in synergistic lithium conduction, while the weaker lithium coordination effect brought by the branched structure and the first core layer jointly realize the efficient dissociation of lithium ions. The polymer arm layer has the same composition as PEO, which significantly improves the compatibility of the superplasticizer-lithium-conducting polymer. At the same time, the polymer arms and the macromolecular lithium-conducting skeleton are entangled with each other to form a film to maintain self-support, and the methylation treatment of the terminal hydroxyl group also significantly improves the high-voltage stability of the polymer electrolyte.
[0038] The beneficial effects of the present invention are as follows: the superplasticizer molecules with a composite topological structure provided by the present invention are applied to the construction of an all-solid polymer electrolyte membrane, which can significantly improve its room temperature lithium conductivity and high-voltage stability without sacrificing the mechanical strength of the membrane, wherein the topological structure of the superplasticizer can be adjusted by regulating the branching degree of the second core layer, thereby achieving precise regulation of the mechanical strength, lithium conductivity and high-voltage stability of the polymer membrane. The room temperature lithium ion conductivity of the composite all-solid electrolyte membrane can reach up to 9.65×10 -5S / cm, and applying it to all-solid-state lithium batteries can enable the corresponding lithium-ion batteries to exhibit excellent room temperature cycle and rate performance. The polymer electrolyte is matched with high-voltage positive electrode materials represented by NCM811, and can achieve stable charging and discharging at room temperature in a wide voltage range of 2.5-4.2 V. The preparation process of the superplasticizer is simple and can be matched with the cast film coating process, effectively solving the major bottlenecks of polymer all-solid-state batteries, such as the difficulty of room temperature ion conduction and poor high-voltage stability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0040] Figure 1 H NMR spectra of HPEI, HPEI-OH and H1P1mP1 (the solvents were D2O and DMSO-d6, respectively);
[0041] Figure 2 The ionic conductivity of polymer electrolyte membranes prepared by blending different superplasticizers with PEO;
[0042] Figure 3 Schematic diagram of the synthesis of H1P1mP1. DETAILED DESCRIPTION
[0043] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0044] For the convenience of explanation, the polymer superplasticizer with a star-shaped topological structure of the present invention is referred to as H x P y mxD z , where H, P, and mP are the abbreviations of C1, C2, and A (branched polyamine, branched polyether, and capped polyethylene glycol monomethyl ether), respectively, and x, y, and z are the codes for different component components.
[0045] Example 1. Preparation of superplasticizer H1P1mP1
[0046] In a three-necked flask, 1 g of branched polyethyleneimine (number average molecular weight 10,000) was fully dissolved in 10 mL of anhydrous methanol. The temperature was raised to reflux under argon protection and 1.05 molar equivalents of glycidol contained in the branched polyethyleneimine was slowly added (the dropping rate was controlled at 150 μL / min). After the addition was completed, the reflux reaction was maintained for more than 4 hours. The product was precipitated in acetone and dried in vacuum at 50°C to obtain a hydroxyl-modified polymer HPEI-OH.
[0047] 2 g HPEI-OH (number average molecular weight 10,000) was dissolved in 20 mL of anhydrous methanol and stirred at room temperature to fully dissolve. Under argon protection, 0.1 molar equivalent of potassium methoxide was injected into the HPEI-OH hydroxyl group dissolved in a small amount of anhydrous methanol by syringe, and continued to stir at room temperature for 1 hour for deprotonation. Then, a vacuum pump was used to remove most of the solvent until it became viscous, and stirring was continued for 1 hour to fully deprotonate. Then, the temperature was gradually raised to 70°C under vacuum conditions, and the solvent was completely drained. When no obvious bubbles were generated in the system, the pumping was stopped and argon protection was restored. The system temperature was raised to 95°C, and the deprotonated HPEI-OH turned into a dark brown highly viscous liquid. 20 mL of anhydrous diethylene glycol dimethyl ether was added to the system with a syringe. After the deprotonated HPEI-OH was fully dissolved, 0.2 g of freshly distilled glycerol was slowly dripped into the system with a peristaltic pump under rapid stirring (the dripping speed was controlled at 75 μL / min). After the dripping was completed, the reaction was maintained at 95°C overnight. Subsequently, the system temperature was lowered to 45°C, 10 mL of methanol was injected to fully dissolve the reaction product and terminate the ionic polymerization reaction, and the solution was passed through a cation exchange resin at a flow rate of 0.2 mL / min to obtain a polyethyleneimine-polyglycidol methanol solution. The solution was dialyzed against water for two days using a dialysis bag with a molecular weight cutoff of 3500 and against ethanol for one day. The product was spin-dried to obtain polyglycidol-modified polyethyleneimine H1P1.
[0048] 1 g mPEG (number average molecular weight 500) was dissolved in 5 mL of anhydrous N,N-dimethylacetamide. The oil bath was heated to 40°C under argon protection, and diphenylmethane diisocyanate (equimolar equivalent to mPEG hydroxyl group, drop rate 150 μL / min) dissolved in 5 mL of anhydrous N,N-dimethylacetamide was slowly dripped into the system. After the dropwise addition was completed, the reaction was maintained at 40°C for 2 hours. Then the system was heated to 60°C, and H1P1 (equimolar equivalent to mPEG hydroxyl group, drop rate 150 μL / min) dissolved in 10 mL of anhydrous N,N-dimethylacetamide was slowly dripped. After the dropwise addition was completed, the reaction was maintained at 60°C for 2 hours, and then cooled to room temperature. The product solution was dialyzed in anhydrous ethanol for two days, the solution was spin-dried, and vacuum dried at 70°C to obtain the product H1P1mP1.
[0049] Example 2. Preparation of superplasticizer H1P2mP1
[0050] The difference from Example 1 is that the mass of glycidol added during the anionic ring-opening polymerization in this example is changed to 0.4 g, and the remaining processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0051] Example 3. Preparation of superplasticizer H1P3mP1
[0052] The difference from Example 1 is that the mass of glycidol added during the anionic ring-opening polymerization in this example is changed to 0.8 g, and the remaining processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0053] Example 4. Preparation of superplasticizer H2P1mP1
[0054] Different from Example 1, the initial polymer used in this example is polyethyleneimine with a number average molecular weight of 25,000, and a dialysis bag with a molecular weight cutoff of 14,000 is used for purification. The remaining processes and process parameters are the same as those in Example 1 and will not be repeated here.
[0055] Example 5. Preparation of superplasticizer H1P1mP2
[0056] The difference from Example 1 is that the number average molecular weight of mPEG used in this example is changed to 1000, and the other processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0057] Example 6. Preparation of superplasticizer H1P1mP3
[0058] The difference from Example 1 is that the number average molecular weight of mPEG used in this example is changed to 5000, and the other processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0059] Example 7. Preparation of superplasticizer H3P1mP1
[0060] The difference from Example 1 is that the number average molecular weight of the branched polyethyleneimine used in this example is changed to 50,000, and a dialysis bag with a molecular weight cutoff of 14,000 is used for purification. The remaining processes and process parameters are the same as those in Example 1 and will not be repeated here.
[0061] Example 8. Preparation of superplasticizer H4P1mP1
[0062] The difference from Example 1 is that the number average molecular weight of the branched polyethyleneimine used in this example is changed to 1800, and the remaining processes and process parameters are the same as those in Example 1, which will not be described again.
[0063] Example 9. Preparation of superplasticizer H2P2mP1
[0064] The difference from Example 1 is that the number average molecular weight of the branched polyethyleneimine selected in this example is changed to 25,000, the mass of glycidol added during the anionic ring-opening polymerization is changed to 0.4 g, and the remaining processes and process parameters are the same as those in Example 1 and will not be repeated here.
[0065] Example 10. Preparation of superplasticizer H2P1mP2
[0066] The difference from Example 1 is that the number average molecular weight of the branched polyethyleneimine used in this example is changed to 25,000, and the number average molecular weight of the mPEG used is changed to 1,000. The remaining processes and process parameters are the same as those in Example 1 and will not be repeated here.
[0067] Example 11. Preparation of superplasticizer H3P3mP3
[0068] The difference from Example 1 is that the number average molecular weight of the branched polyethyleneimine selected in this embodiment is changed to 50,000, the mass of glycidol added during the anionic ring-opening polymerization is changed to 0.8 g, the number average molecular weight of mPEG is changed to 5,000, and a dialysis bag with a molecular weight cutoff of 14,000 is used for purification. The remaining processes and process parameters are the same as those in Example 1 and are not repeated here.
[0069] Example 12. Preparation of superplasticizer H4P3mP1
[0070] The difference from Example 1 is that the number average molecular weight of the branched polyethyleneimine used in this example is changed to 1800, the mass of glycidol added during the anionic ring-opening polymerization is changed to 0.8 g, and the remaining processes and process parameters are the same as those in Example 1 and will not be repeated here.
[0071] Example 13. Superplasticizer H5P1mP1
[0072] The difference from Example 1 is that the C1 macromolecule used in this example is a hyperbranched polyamide-amine, and the remaining processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0073] Example 14. Superplasticizer H6P1mP1
[0074] The difference from Example 1 is that the C1 macromolecule used in this example is branched polyethylene glycol amine, and the remaining processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0075] Example 15. Superplasticizer H1P4mP1
[0076] The difference from Example 1 is that the C2 monomer selected in this example is propylene oxide, and the remaining processes and process parameters are the same as those in Example 1, which will not be described again.
[0077] Example 16. Superplasticizer H1P5mP1
[0078] The difference from Example 1 is that the C2 monomer selected in this example is polybutylene oxide, and the remaining processes and process parameters are the same as those in Example 1, which will not be described again.
[0079] Example 17. Superplasticizer H1P6mP1
[0080] The difference from Example 1 is that the C2 monomer selected in this example is 3-methyl-3-oxetanemethanol, and the remaining processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0081] Comparative Example 1. Preparation of superplasticizer H1P0mP1
[0082] Different from Example 1, in the synthesis process of the superplasticizer, there is no HPEI-OH to initiate the anionic ring-opening polymerization of the glycidol monomer, and HPEI-OH directly reacts with the mPEG isocyanate group. The remaining processes and process parameters are the same as those in Example 1 and are not repeated here.
[0083] Comparative Example 2. Preparation of superplasticizer H1mP1
[0084] Different from Example 1, in the synthesis process of the superplasticizer, there is no HPEI hydroxylation and HPEI-OH-induced anionic ring-opening polymerization of glycidol monomer in this comparative example. The urea bond is directly formed by the reaction of the HPEI amino group with the mPEG isocyanate group. The remaining processes and process parameters are the same as those in Example 1 and are not repeated here.
[0085] Comparative Example 3. Preparation of superplasticizer H0P1mP1
[0086] Different from Example 4, this comparative example uses linear polyethyleneimine with a number average molecular weight of 25,000 as the modified main body, and the remaining processes and process parameters are the same as those in Example 4, which will not be repeated here.
[0087] Comparative Example 4. Preparation of superplasticizer H1P1mP0
[0088] The difference from Example 1 is that ethylene glycol monomethyl ether is used to replace mPEG in this example, and the remaining processes and process parameters are the same as those in Example 1, which will not be repeated here.
[0089] Test Example 1. Chemical composition characterization of synthetic superplasticizer samples
[0090] Liquid NMR hydrogen spectrum is used to analyze the group composition and molecular weight of the synthesized superplasticizer. Typical sample NMR hydrogen spectrum characterization is as follows Figure 1 shown.
[0091] Depend on Figure 1 It can be seen that the raw material hyperbranched polymer HPEI has a broad peak composed of many superimposed methylene groups at 2.5 ppm. The hydroxyl-modified sample HPEI-OH has two new multiple signal peaks at 3.5 ppm and 3.7-4.0 ppm, corresponding to the hydrogen atom signals on the methylene and methyl groups in the glycidol structure grafted on the HPEI shell. The H1P1mP1 superplasticizer, which is grafted with glycidol branched shells and linear polyether end groups in sequence, retains the original peak of HPEI. On the basis of the presence of a benzene ring signal peak introduced by an isocyanate crosslinker near 7.0-7.5 ppm, there is a significant single peak of the methyl signal of the polyethylene glycol monomethyl ether arm end at 3.36 ppm, which fully demonstrates that the sample was successfully synthesized.
[0092] Test Example 2. Preparation of a composite all-solid polymer electrolyte membrane containing the product of the above example
[0093] The composite all-solid electrolyte membrane is prepared by the following method:
[0094] (1) The all-solid electrolyte membrane is prepared by tape casting. The electrolyte membrane consists of a polymer lithium-conducting matrix and a lithium salt. The lithium salt is lithium bis(trifluorosulfonyl)imide (LiTFSI). The polymer lithium-conducting matrix consists of a high molecular weight lithium-conducting skeleton (molecular weight 1000000 PEO) and a superplasticizer HxPymPz.
[0095] (2) Weigh 0.138 g of superplasticizer HxPymPz, 0.207 g of lithium-conducting framework PEO and 0.25 g of lithium salt (lithium bis(trifluoromethanesulfonyl imide)) and dissolve them in 3 g of N-methylpyrrolidone. Heat at 60 degrees and stir for 2 hours, then stir at room temperature for 12 hours to form a homogeneous polymer concentrated solution.
[0096] (3) In a drying room with a relative humidity of less than 20%, the above-mentioned polymer electrolyte concentrated solution is poured onto a release paper, and quickly coated with an automatic film scraper adjusted to a specific thickness to obtain a polymer electrolyte wet film; the wet film is dried by air-blast infrared radiation to fully remove the residual solvent to obtain an electrolyte dry film; the electrolyte dry film is hot-rolled in a heating environment of 70°C and a rolling thickness of 50 μm, and then cooled and demolded to obtain the desired all-solid polymer electrolyte membrane.
[0097] Test Example 3. Determination of ionic conductivity of composite all-solid polymer electrolyte membrane
[0098] A blocking electrode with a stainless steel gasket / all-solid composite electrolyte / stainless steel gasket structure was constructed. The ionic conductivity of the all-solid polymer electrolyte membrane prepared in the above embodiments and comparative examples was tested at different temperatures by means of electrochemical impedance spectroscopy and in combination with the corresponding calculation formula. The test results of some embodiments are shown in Tables 1 and Figure 2 .
[0099] Table 1. Temperature-variable ionic conductivity of composite all-solid electrolytes prepared by some examples and comparative example 1
[0100]
[0101] The test results show that the room temperature ionic conductivity of the all-solid polymer electrolyte prepared by the superplasticizer prepared in Example 11 can exceed 9.65×10 -5 S / cm, which is 8 times higher than the comparative example of adding traditional plasticizer electrolyte, and its ionic conductivity at different temperatures is higher than the comparative example, which has strong practical application value. In addition, compared with other embodiments, it can be seen that the influence of superplasticizer on the lithium conductivity of polymer electrolyte is closely related to its branched structure and core-shell composition. The composite solid electrolyte membrane prepared by the type of polymer within the scope of the present invention, the type of superplasticizer and different component ratios all have high ionic conductivity.
[0102] Test Example 4. Composite all-solid polymer electrolyte membrane charge and discharge performance test
[0103] The composite all-solid-state electrolyte membrane prepared above was assembled into a lithium iron phosphate / Li metal half-cell and its 0.1 C charge-discharge cycle performance at room temperature was tested. The charge-discharge performance of some embodiments and comparative examples of Example 2 is shown in Table 2.
[0104] Table 2. Cyclic performance test of lithium iron phosphate / Li battery assembled by preparing composite solid electrolyte membrane in some embodiments and comparative examples.
[0105]
[0106] Table 3. Battery performance test of NCM811 battery after 100 cycles
[0107]
[0108] It can be seen from the table that the lithium iron phosphate and NCM811 solid-state full batteries assembled with the organic composite all-solid-state electrolyte prepared using the superplasticizer molecules synthesized by the present invention have higher capacity, better capacity retention rate and higher coulombic efficiency than the comparative electrolyte.
[0109] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A polymer superplasticizer having a star-shaped topological structure, characterized in that: The superplasticizer comprises three parts: a first core layer, a second core layer and a polymer arm; The first core layer is one of branched polyethyleneimine, branched polyamide-amine, and branched polyethylene glycol amine; The second core layer is one or more of branched polyglycidol, branched polypropylene oxide, branched polybutylene oxide, and branched poly 3-methyl-3-oxetane methanol; The polymer arm is a difunctional isocyanate-terminated polyethylene glycol monomethyl ether, and is bonded to the second core layer via a urea bond or a urethane bond; The difunctional isocyanate is selected from toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, isophorone diisocyanate, and m-xylylene diisocyanate; The preparation process of the polymer superplasticizer with a star-shaped topological structure includes preparation of a macromolecular initiator, initiation of polymerization, termination of polymerization, end group modification and product purification; The preparation of the macromolecular initiator includes two steps: hydroxylation of the first core layer macromolecules and deprotonation of the hydroxylated macromolecules; (1) Hydroxylation of the first core layer macromolecule: Under the protection of inert gas, the branched first core layer macromolecule is dissolved in a solvent and heated, and then a certain amount of glycidol monomer is added dropwise. After the addition is completed, the reaction is allowed to proceed for a period of time, and then the system is cooled to room temperature, acetone is precipitated, and the product is dried in vacuum; (2) Deprotonation of hydroxylated macromolecules: The hydroxylated first core layer macromolecules are fully dissolved in the solvent, and a certain amount of Lewis base solution is injected under the protection of inert gas. Deprotonation is carried out at 35-45°C, and then the viscous liquid with most of the solvent is depressurized and continued to deprotonate for a period of time. Finally, the solvent is dried at 55-65°C to obtain a foamy deprotonated macromolecular initiator; The above-mentioned initiation polymerization process can be divided into two steps: secondary dissolution of the macromolecular initiator and addition of the second core layer monomer; the obtained foamy macromolecular initiator is added with a high-boiling point polar aprotic solvent at a certain temperature to be fully dissolved, and then the temperature is raised to the polymerization temperature, and the second core layer monomer is slowly added dropwise into the system under high-speed stirring. After the addition is completed, the polymerization reaction takes more than 6 hours; the second core layer monomer includes one or more of glycidol, propylene oxide, butylene oxide, and 3-methyl-3-oxetane methanol.
2. The process for preparing a polymer superplasticizer having a star-shaped topological structure according to claim 1, characterized in that: During the hydroxylation of the first core layer macromolecules, the molecular weight of the first core layer macromolecules is between 1800 and 200000; the solvent is one or more of anhydrous methanol, anhydrous ethanol, and anhydrous tetrahydrofuran, and the concentration range of the polymer solution prepared using the solvent is 0.025 g / mL to 0.5 g / mL; the heating temperature of the polymer solution is 40 to 65 °C; the amount of glycidol monomer added is the amount of all active hydrogen and other substances of the first core layer macromolecules, and the dripping speed is 0.15 mL / min to 0.6 mL / min; In the deprotonation process of the hydroxylated macromolecule, the solvent is one or more of anhydrous methanol, anhydrous ethanol, and anhydrous tetrahydrofuran; the solvent used for the Lewis base solution is consistent with the solvent of the hydroxylated macromolecule, and the concentration of the Lewis base solution is 3-5 mol / L; the above-mentioned deprotonating agent can be one or more of potassium methoxide, sodium methoxide, sodium hydride, and cesium hydroxide, and the added amount is 0.05-1 of the molar equivalent of the hydroxyl group input into the polymer.
3. The process for preparing a polymer superplasticizer having a star-shaped topological structure according to claim 1, characterized in that: The termination polymerization process can be divided into two steps: active initiator end group quenching and proton exchange; specifically, a certain volume of anhydrous methanol is added to the reaction system to quench the reaction, the product solution flows through a pre-activated strong acid cation exchange resin at a certain flow rate to remove the end group metal ions, and then the solvent is spin-dried, and the product is vacuum dried to obtain a polyamine-ether core-shell structure hyperbranched polymer.
4. The process for preparing a polymer superplasticizer having a star-shaped topological structure according to claim 1, characterized in that: The above-mentioned end group modification process can be divided into three steps: polyethylene glycol monomethyl ether end group activation, polyurethane reaction and product purification.
5. The polymer superplasticizer with a star-shaped topological structure as claimed in claim 1 is used to prepare an all-solid-state polymer electrolyte.
Citation Information
Patent Citations
Super plasticizer with composite topological structure and application of super plasticizer in electrolyte membrane of all-solid-state lithium metal battery
CN114634618A
Multibranched polymer and manufacturing method thereof
JP2009185179A